Respostas
respondido por:
1
Oi Samara,
(x-5).(-3)+6=-2x+1
(-3).(x-5)+6=-2x+1
-3x+15+6=-2x+1
-3x+2x=1-21
-x=-20 .(-1)
x=20
Bons estudos!!
(x-5).(-3)+6=-2x+1
(-3).(x-5)+6=-2x+1
-3x+15+6=-2x+1
-3x+2x=1-21
-x=-20 .(-1)
x=20
Bons estudos!!
respondido por:
0
Olá,
(x-5)(-3)+6 = -2x+1
-3x+15+6 = -2x+1
-3x+21 = -2x+1
-3x+2x = 1-21
-x = -20
-x/-1 = -20/-1
x = 20
(x-5)(-3)+6 = -2x+1
-3x+15+6 = -2x+1
-3x+21 = -2x+1
-3x+2x = 1-21
-x = -20
-x/-1 = -20/-1
x = 20
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás